New Testament textual criticism: the application of thoroughgoing principles ; essays on manuscripts and textual variation - Elliott, J. K. (Novum Testamentum / Supplements, 2010)
Methodology. The New Testament text in the second century : a challenge for the twenty-first century -- The nature of the evidence available for reconstructuring the text of the New Testament in the second century -- Thoroughgoing eclecticism -- Manuscripts. Singular readings in the Gospel text of Papyrus 45 -- T.C. Skeat on the dating and origin of Codex Vaticanus -- Codex Bezae and the earliest Greek papyri -- A Greek-Coptic (Sahidic) fragment of Titus-Philemon (0205) -- The Greek manuscript heritage of the Book of Acts -- Manuscripts of the Book of Revelation collated by H.C. Hoskier -- The distinctiveness of the Greek manuscripts of the Book of Revelation -- Recent Oxyrhynchus papyri -- Studies and praxis. The influence of G.D. Kilpatrick -- Specific variants -- Mark 1:1-3 : a later addition to the Gospel? -- The position of the verb in Mark with special reference to Mark 13 -- The last twelve verses of Mark : original or not? -- The text of Acts in the light of two recent studies -- An eclectic study of the Book of Acts -- The language and style of the concluding doxology to the Epistle to the Romans -- The divine names in the Corinthian letters -- The conclusion of the pericope of the healing of the leper and Mark 1:45 combined with Is [ho exelthōn] a title for Jesus in Mark 1:45? and The healing of the leper in the synoptic parallels -- Anna's age (Luke 2:36-37) -- Is post-baptismal sin forgivable? -- The parable of the two sons : text and exegesis -- Paul's teaching on marriage in 1 Corinthians : some problems considered -- An examination of the text and apparatus of three recent Greek synopses -- Textual criticism, assimilation and the Synoptic Gospels -- Printed editions of Greek synopses and their influence on the Synoptic problem -- Resolving the Synoptic problem using the text of printed Greek synopses -- Reviews of recent critical editions. The Editio critica maior -- The United Bible Societies' fourth revised edition and Nestle-Aland 27 -- The International Greek New Testament Project's volumes on the Gospel of Luke -- The Marc Multilingue Project -- Appendix. Manuscripts, the codex and the canon